Dynamics of heart rate variability depending on the type of anesthesia during surgery for anterior abdominal wall hernias - Ж.О. Ушневич; М.О. Гарбар (Медицина неотложных состояний)
Background. Heart rate variability (HRV) is a non-invasive method of analyzing the response of the entire body to surgical stress. The adequacy of the autonomic nervous system response during the perioperative period involves both the initial reserves of the body and the physiology of anesthesia method. HRV is used to predict perioperative complications, especially cardiac ones, mortality, and duration of inpatient treatment. The purpose of the study was to perform a comparative analysis of the dynamics of heart rhythm variability at the stages of elective surgery for anterior abdominal wall hernias depending on the type of anesthesia. Materials and methods. Ninety-one patients with anterior abdominal wall hernias were examined and treated. They were divided into 3 groups according to the method of anesthesia (general, neuraxial and regional blockades). Patients underwent 24-hour ECG monitoring with assessment of HRV. Changes in HRV were evaluated during the surgery: the dynamics of 30 intervals of 5 minutes, a total of 2 hours and 30 minutes were chosen. The monitoring was conditionally divided into 3 stages — the initial, the main one, and the end of the surgery. Results. Under general anesthesia, the median SDNN and pNN50 by the end of the operation were significantly lower than the baseline. Under regional and neuraxial anesthesia, they increased compared to the preoperative level or returned to the baseline. In patients with general anesthesia, LF/HF median decreased statistically significantly until the end of the surgery, and under regional and neuraxial anesthesia, it increased and exceeded the preoperative level. In all patients, along with a decrease in total HRV, there was a reduction in the influence of both sympathetic and parasympathetic parts of the autonomic nervous system on cardiac rhythm. But in general anesthesia, HRV reduction was maintained until the end of the follow-up period, in contrast to patients with epidural anesthesia and regional blockades who reported an increase in both sympathetic and parasympathetic activity until the end of the surgical intervention. Conclusions. The dynamics of HRV during neuraxial and regional analgesia reflects the most physiological response of the autonomic nervous system of a patient with comorbid cardiovascular pathology during elective surgery for anterior abdominal wall hernias.